A surface and catalytic study of heterogenised Os3(CO) 12 species in MCM-41 structures - Caps, V; Paraskevas, I; Tsang, S (2003)
Immobilised Os species prepared via chemical vapour deposition (CVD) of Os3(CO)12 onto MCM-41 are active and selective catalysts for the dihydroxylation of trans-stilbene in acetone and water, using N-methylmorpholine N-oxide as the oxidant. A detailed temperature programmed decomposition study of the solids enables to identify the active sites as Osx(CO)y surface species. The initial loading of the MCM-41 with the trinuclear precursor, as well as the temperature of the post-synthesis oxidising treatment, are found to have a significant impact on the structure/geometry of the resulting surface species, and thus their catalytic properties. We show how it is also affected by the confined environment of the MCM-41 mesopores and especially the curvature of the 30 Å diameter channels. Finally, a careful study of the catalytic properties of the materials together with a study of the reactivity of the reaction products under similar conditions enable to suggest a mechanism involving the reaction of the oxidant with the osmium carbonyl surface species to form the catalytically active Os-oxo sites, and the formation of an osmoate-type species (through adsorption of the alkene onto the Os-oxo site) which subsequently reacts with the solvent to produce the diol. © 2003 Elsevier B.V. All rights reserved.